2006
DOI: 10.1161/01.res.0000219904.43852.3e
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin-Induced Decrease in Ca 2+ Sensitivity of Contraction in Mouse Tail Arteries Is Attributable to cAMP-Dependent Dephosphorylation of MYPT1 and Activation of Myosin Light Chain Phosphatase

Abstract: Abstract-Urocortin, a vasodilatory peptide related to corticotropin-releasing factor, may be an endogenous regulator of blood pressure. In vitro, rat tail arteries are relaxed by urocortin by a cAMP-mediated decrease in myofilament Ca 2ϩ sensitivity through a still unclear mechanism. Here we show that contraction of intact mouse tail arteries induced with 42 mmol/L KCl or 0.5 mol/L noradrenaline was associated with a Ϸ2-fold increase in the phosphorylation of the regulatory subunit of myosin phosphatase (SMPP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…Phosphorylation of Thr696 has been associated with inhibition of the catalytic activity of MLCP, and the phosphorylation of Thr850 is associated with inhibition of the holoenzyme binding to myosin (43). Studies show that ROCK may inhibit MLCP activity through the phosphorylation of MYPT1 at either Thr695 (8,17,18,40), Thr850 (24,35,50), or both (31,48). In the present study, we found that the phosphorylation of MYPT1 at both Thr696 and Thr850 stimulated by endothelin-1, which indirectly stimulates ROCK through G protein-dependent activating RhoA/ROCK pathway (49), was greater in chronically hypoxic pulmonary arteries than in control vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of Thr696 has been associated with inhibition of the catalytic activity of MLCP, and the phosphorylation of Thr850 is associated with inhibition of the holoenzyme binding to myosin (43). Studies show that ROCK may inhibit MLCP activity through the phosphorylation of MYPT1 at either Thr695 (8,17,18,40), Thr850 (24,35,50), or both (31,48). In the present study, we found that the phosphorylation of MYPT1 at both Thr696 and Thr850 stimulated by endothelin-1, which indirectly stimulates ROCK through G protein-dependent activating RhoA/ROCK pathway (49), was greater in chronically hypoxic pulmonary arteries than in control vessels.…”
Section: Discussionmentioning
confidence: 99%
“…15 The role of endothelium in urocortin effect varied depending on the arteries and apparently on the type of the contraction stimuli. [15][16][17][18][19] Moreover diverse concentrations of urocortin were used to relax different vessels, which generally were higher than the physiological range described in human plasma membrane. 38 In fact, a full relaxation was induced by 10 nmol/L urocortin in basilar artery 18 ; 10 to 30 nmol/L of urocortin induced maximum relaxation in U46619 precontracted rat coronary and human mammary artery, [15][16][17] 100 nmol/L produced 60% relaxation of tail artery precontracted with high K ϩ , 19 meanwhile up to 206 nmol/L of urocortin caused a moderate decrease of coronary perfusion pressure in isolated rat heart.…”
Section: Discussionmentioning
confidence: 99%
“…myosin phosphatase is involved in lowering sensitivity to intracellular Ca 2+ by 2 -agonists, and this process can also be achieved via cAMP-dependent and -independent pathways [68]. PKA inactivates RhoA [77] and MYPT1 [78]. In addition to this observation, Rho-kinase inhibitors enhance relaxation by 2 -agonists in airway smooth muscle [79].…”
Section: Roles Of Ca 2+ Sensitizationmentioning
confidence: 99%